Associations of time to the operating room on outcomes in odontogenic infection - Jeffrey N. James; Ryan Bloomquist; Kiara Brown; Stephen Looney; Dylan Walker; Tyler Day (BMC Oral Health)
Abstract The purpose of this study was to determine if there were correlations between the length of time from hospital admission to surgical intervention and the frequency of complications in patients with odontogenic infections. While odontogenic infection is well studied in terms of interventions and outcomes, less is known about hospital utilization and resource burden of odontogenic infection with respect to timeliness to intervention. A retrospective cohort analysis was used to examine correlations between time from admission to surgical intervention and clinical outcomes. Patients included in this study were divided into three categories of length of time to the operating room: 0–12 h, 12.1–24 h, and greater than 24 h. Time of admission, time of surgical intervention, patient demographics, admission lab values, and space involvement were measured and compared to the primary outcome variables including complications of intubation attempts and type, ICU admission, length of hospitalization, number of changes in antibiotic therapy, and frequency of return to the operating room. We found that the length of time to the OR had a statistically significant association with length of hospital stay (p = 0.003) and number of changes in antibiotic therapy (p = 0.033). While overall length of hospital stay is inherently dependent on length of time to the OR, this relationship highlights the importance of timeliness to definitive intervention in order to reduce hospital burden. This study provides evidence on how to prioritize odontogenic infections in a hospital setting. We recommend treating odontogenic infection in less than 24 h from the time of admission in order to reduce costs and improve outcomes for patients.